Spinal cord fractalkine (CX3CL1) signaling is critical for neuronal sensitization in experimental nonspecific, myofascial low back pain - Sessler, Katharina; Blechschmidt, Vivian; Hoheisel, Ulrich; Mense, Siegfried; Schirmer, Lucas; Treede, Rolf-Detlef (Journal of neurophysiology, 2021)
Download figureDownload PowerPoint
Gesehen am /20.09.2021